FROM THE HISTORY OF THE INTELLECTUAL LEGACY OF THE GREAT KHWARIZMIS OF KHOREZM - Hojiakbar Xamidov (International Journal of Literature and Language Studies, 2026)
Abstract: This article analyzes the lives and the scholarly and educational-pedagogical legacy of five great scholars who emerged from the land of Khorezm and became renowned throughout the world under the epithet “al-Khwarizmi”: Abu Abdullah Muhammad ibn Musa al-Khwarizmi, Abu Bakr al-Khwarizmi, Abu Abdullah al-Khwarizmi, Haydar Khwarizmi, and Hafiz Khwarizmi. The study examines their achievements in the exact sciences, the encyclopedic sciences, and literature, as well as their ethical and educational views. The article aims to demonstrate the contribution of the scholars of Khorezm to the development of both Eastern and Western civilization.